Nilai-Nilai Pendidikan Karakter Peduli Sosial dalam Film Animasi Upin dan Ipin (Musim Sembilan Tajuk Kedai Makan Upin dan Ipin) - Andriana Ridho, Murdianto (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2019)
The weakening of the character of social care is shown by the increasingly widespread individualism and various other selfish and narcissistic acts. One way to teach the value of social care to the community, especially children is through animated films. Animated Film Upin and Ipin is a film that contains the value of education and is packaged as an attractive medium for children and adults. Therefore this thesis reports the results of the study with the formulation of the problem:(1) what are the values ​​of education contained in the film Upin dan Ipin Season 9 Tajuk Kedai Makan Upin dan Ipin, (2) how the values ​​of social care character education in the filmUpin dan Ipin Season 9 Tajuk kedai makan Upin dan Ipin? Result:The educational value contained in the animated film Upin and Ipin season 9 Kedai Makan Upin dan Ipin includes 4 educational values, including the value of religious education, the value of moral education, the value of social education, and the value of cultural education. The film has a very dominant social character character throughout the film, both in the form of dialogue and scenes in it.